IMMUNOLOGICAL DETECTION OF EPSTEIN-BARR VIRUS ANTIGEN AND EVALUATION OF TNF-Α AND IL-10 IN PATIENTS WITH Β-THALASSEMIA MAJOR - Mahmood, Ghofran Saad; Al-Taie, Anmar A (PT. Antis International Publisher, 2025)
Objective: This study aims to detect Epstein–Barr virus antigens using the ELISA technique and to evaluate the immune status by measuring the levels of inflammatory cytokines, namely Tumor Necrosis Factor (TNF) and Interleukin-10 (IL-10). Method: This study was conducted on 150 patients previously diagnosed with major β-thalassemia by physicians at the hospital. Special kits were used to detect viral antigens, in addition to other kits used for measuring cytokine levels. Statistical analysis was also performed to evaluate the cytokine data. Results: The virus was detected in 82% of the total number of patients. The highest rate was recorded in patients aged between 11-20 years and females showed a higher infection rate compared to males. Regarding cytokines, there was a statistically significant increase in the levels of Interleukin-10 and Tumor Necrosis Factor in patients compared to the control group, p-values of 0.0048 and 0.0035, respectively. Novelty: The results revealed the presence of immune regulatory dysfunction in this group of patients, as they exhibited signs of both immune activation and suppression simultaneously. This underscores the importance of continuous immunological monitoring for this category of patients.